Investigation into the seamless construction for hundred-meter scale super-length raft structure based on magnesia expansive agent concrete - Han, Bin; Wang, Huichao; Liao, Hong; Dai, Chao; Zhao, Yunpeng; Xu, Wenlong; Zhou, Guojing; Shi, Chuandong (Frontiers in Materials, 2024)
This research introduces an innovative construction method based on magnesia expansive agent concrete for the seamless construction of hundred-meter scale super-length raft structures, corroborated by the on-site test. The basic principle of this construction method is to use the pre compression stress generated by magnesia expansive agent to offset temperature and shrinkage stress. A temperature-strain monitoring system was employed to gather data, affirming the technique's applicability and safety. Through the examination of temperature and strain dispersion trends in super-length raft structure, recommendations for the configuration of temperature-strain sensors have been put forth. Through the scrutiny of the temporal evolution pattern of temperature, the specific temporal and spatial coordinates that warrant particular vigilance during the surveillance of the raft's inner-surface temperature difference were identified. Upon evaluating the correlation between strain dispersion and strain-temperature differential in the raft's thickness dimension, a novel temperature control index (the bottom-surface temperature difference) was introduced. The threshold for this metric was established at 30℃, derived from empirical test outcomes conducted on-site. Furthermore, the critical regions for monitoring the bottom-surface temperature difference were specified.